Plan mejoramiento para el area de mercadeo dela empresa Construpunto (2015)
In Colombia the construction sector has been progressive with the development of road, railway, production of gray cement, ready-mix concrete and construction of buildings for housing and office infrastructure, and the country is a pioneer in Latin America in this sector, being above Latin American powers like Mexico, Brazil and Chile. At the regional level, at the level of the coffee axis, comprising the departments of Caldas, Risaralda and Quindio, according to the Central Bank in its report "composition of the economy of the coffee-growing region of Colombia," the primary sector economy of this region is manufacturing, followed by construction, and stresses that both sectors have maintained growth in recent years, thanks mainly to the development of the capital cities and urban centers. From this, the company Construpunto being dedicated to the marketing of construction products, through a period of success in sales by private treaty, as the construction sector in the city of Armenia has been a significant rise in the last five years according to DANE (Caracol, 2014), however direct sales, where people interact directly with company personnel (proposed by the Colombian Association of direct selling ACOVEDI concept) are limited, so the obvious concern of the directors of the company is shown, looking for ways to increase such sales. Therefore the improvement plan marketing area aims to direct sales, and direct customer interaction; that they are important for the new stage in which the company is therefore making the internship offers possible solutions in order to improve their processes and continue generating value. Keywords: Marketing, value, strategies and direct sales